Persepsi Mahasiswa Akuntansi Terhadap Profesi Akuntan Publik - Herlin Herlin; Marlinda Sari (Agregat: Jurnal Ekonomi dan Bisnis, 2018)
This research aims to gain the perception or attitude of the students towards the profession of public accounting accounting. This research was done at the University of Bengkulu Dehasen addressed to the accounting student with the number of respondents as many as 55 people. To get the perception of this study uses census with sampling method research tool questionnaire presented to students by way of accounting to meet directly and ask for the willingness of the time to fill out the questionnaire provided. The results of this study proves that the most dominant factor affect the perception of accounting students of Dehasen Bengkulu University to the profession of public accountant is the personality and professional recognition. While the factor of financial reward and work environment Does not affect the perception of accounting students of Dehasen University of Bengkulu to the public accountant profession